Sosialisasi Dan Pelatihan Kepada Anak Sekolah Minggu Jemaat Betlehem GPI Kota Sorong Dengan Tema “Semangat Bersama Dalam Membangun Jiwa Kepemimpinan Pada Anak Sejak Dini” - Adolfina Putnarubun; Arce Y. Ferdinandus; Susana M. W. Muskitta; Edward Clan (CV. Multi Kreasi Media, 2023)
The responsibility for fostering children in the community environment is not only the task of parents, but the school environment and community environment as well as the church also play an important role in providing a positive learning environment for children. The creation of a good environment for the growth and development of children will slowly have a positive impact on the child's soul in developing his leadership spirit from an early age. For that, what children need is space to be able to explore themselves. The enthusiasm of children to explore the world begins at an early age. Looking at the context of children's development in the church environment in particular, we as a team of servants who are Lecturers and Students as adult individuals in the field of education, feel the need to contribute in fostering young children, adults and teenagers who are in the congregation of Sorong City , one of which is the GPI Bethlehem Congregation which is our target as a service team. The theme